METHODS FOR IMPROVING THE STABILITY AND EFFICIENCY OF COMMUNICATION NETWORKS IN DIFFICULT CONDITIONS - HALYKA, KARINA; BOYKO, OLEG; MADINOV, MYKOLA; VOLOSHYN, VASYL; HALAHAN, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article is devoted to the study of methods for increasing the stability and efficiency of communication networks in difficult conditions, with an emphasis on monitoring the technical condition of the infrastructure and optimizing network operation using advanced technologies. The purpose of the study is to create a comprehensive communication network management system that combines equipment condition monitoring, adaptive resource management and the use of highly efficient modulation formats to increase network throughput and stability. To achieve the goal, a multi-level approach to monitoring was used, which includes the analysis of network node parameters at the local, regional and global levels with the use of threshold values to assess the technical condition. The study considers coherent modulation formats, in particular DP-QPSK, and Flexgrid technology for flexible spectral management. Multi-agent system modeling is based on the principles of distributed artificial intelligence, which provides synergistic assessment of network parameters. The main scientific results include the development of a monitoring model with multiple closed control loops, which allows detecting and isolating failures, predicting risks and optimizing resource allocation. The introduction of the DP-QPSK format provided an increase in spectral efficiency, allowing the transmission of 4 bits per symbol without changing the frequency plan, and Flexgrid technology in combination with software-defined transponders (SDT) made it possible to adaptively adjust the channel width depending on the traffic, increasing the network’s resilience to overloads. The prospects for further research are related to the improvement of multi-agent systems by integrating machine learning for anomaly prediction, as well as the development of ultra-complex modulation formats, such as DP-256QAM, to achieve data rates of up to 1 Tbit/s. A separate direction is the optimization of photonic integration to create energy-efficient and compact solutions that will facilitate the scaling of complex communication networks in the future.